2006
DOI: 10.1152/ajpregu.00129.2006
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin-releasing peptide, food intake, and hydromineral balance in goldfish

Abstract: A potential role for prolactin-releasing peptide (PrRP) in appetite regulation and hydromineral balance in goldfish was examined. PrRP was found to be expressed in discrete regions of the goldfish brain, in particular, the hypothalamus. Intraperitoneal (IP) or intracerebroventricular administration of PrRP had dose-dependent effects to suppress food intake in goldfish. Hypothalamic PrRP mRNA expression significantly increased after feeding, as well as after 7 days of food deprivation. Refeeding fish after 7 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…This contrast between chicks and mammals has also been reported for ghrelin and growth hormone-releasing hormone, both of which inhibit feeding in chicks, yet stimulate it in rats (Vaccarino et al 1985, Furuse et al 2001, Nakazato et al 2001. In goldfish, hypothalamic PrRP mRNA expression is modified by feeding status, and either intraperitoneal or ICV administration of fish PrRP peptide has been shown to suppress food intake (Kelly & Peter 2006). It is therefore important to keep in mind that while an evolutionarily conserved role of RFamides in the regulation of feeding behaviour seems clear, the specific actions can vary greatly between class and species.…”
Section: Prrp Familymentioning
confidence: 71%
“…This contrast between chicks and mammals has also been reported for ghrelin and growth hormone-releasing hormone, both of which inhibit feeding in chicks, yet stimulate it in rats (Vaccarino et al 1985, Furuse et al 2001, Nakazato et al 2001. In goldfish, hypothalamic PrRP mRNA expression is modified by feeding status, and either intraperitoneal or ICV administration of fish PrRP peptide has been shown to suppress food intake (Kelly & Peter 2006). It is therefore important to keep in mind that while an evolutionarily conserved role of RFamides in the regulation of feeding behaviour seems clear, the specific actions can vary greatly between class and species.…”
Section: Prrp Familymentioning
confidence: 71%
“…To coordinate hyperosmoregulatory functions in various tissues, osmosensitive mechanisms play an essential role in controlling PRL secretion. Although there are several reports that PRL release is under hypothalamic control, the relationship between these regulatory pathways and osmoregulation is still unclear (11,15,22,30,31,40).Previous studies have shown that PRL cells of tilapia are intrinsically responsive to changes in extracellular osmolality (12,23,32,37). The release of PRL from dispersed PRL cells is stimulated by physiologically relevant decreases in extracellular osmolality (36), a response that is closely related to cell volume changes (33,34,45), and is consistent with the hyperosmoregulatory role of PRL.…”
mentioning
confidence: 99%
“…To coordinate hyperosmoregulatory functions in various tissues, osmosensitive mechanisms play an essential role in controlling PRL secretion. Although there are several reports that PRL release is under hypothalamic control, the relationship between these regulatory pathways and osmoregulation is still unclear (11,15,22,30,31,40).…”
mentioning
confidence: 99%
“… a Rat (41) . b Chicken (5) . c Mudskipper (12) . d Sea bream (14) . e Goldfish (45) . +: Definite expression; –: little or nothing .Blank columns indicate “not examined.” Distribution of PrRP has not yet been investigated in teleost . In rats, PrRP mRNA expression is also observed in thymus, trachea, submandibular gland, adrenal gland, and uterus (see PrRP and PrRP-R) .…”
Section: Distribution Of Prrp Prrp2 and Their Receptorsmentioning
confidence: 99%
“…PrRP2 mRNA is distributed in the central nervous system in non-mammalian vertebrates (5, 12, 14, 45, 46) (Table 1). Further, a histological survey has been performed only in teleosts using the antisera against teleost PrRP2 whose cross-reactions with PrRP are unclear.…”
Section: Distribution Of Prrp Prrp2 and Their Receptorsmentioning
confidence: 99%